2003
DOI: 10.1103/physreva.68.042308
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic Rydberg states as direction indicators

Abstract: The orientation in space of a Cartesian coordinate system can be indicated by the two vectorial constants of motion of a classical Keplerian orbit: the angular momentum and the Laplace-Runge-Lenz vector. In quantum mechanics, the states of a hydrogen atom that mimic classical elliptic orbits are the coherent states of the SO(4) rotation group.It is known how to produce these states experimentally. They have minimal dispersions of the two conserved vectors and can be used as direction indicators. We compare the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 16 publications
(47 reference statements)
0
30
0
1
Order By: Relevance
“…It should be noted that estimating the relative angle between a pair of SU(2) coherent states is of particular importance because estimating the eccentricity of an elliptic Rydberg state of a Hydrogen atom is an instance of the same problem [27]. Rydberg states are significant because they can be prepared experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that estimating the relative angle between a pair of SU(2) coherent states is of particular importance because estimating the eccentricity of an elliptic Rydberg state of a Hydrogen atom is an instance of the same problem [27]. Rydberg states are significant because they can be prepared experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…where the explicit expressions for ξ(Λ,k) are given by Lindner, Peres, and Terno (2003) and Bergou, Gingrich and Adami (2003). The superselection rule that was mentioned above makes it impossible to define a reduced density matrix in the usual way Lindner, Peres and Terno, 2003).…”
Section: Photonsmentioning
confidence: 99%
“…In previous work, it was shown that by exchanging a single quantum system between Alice and Bob, a reference frame can be transmitted from Alice to Bob [21,22]. This requires implementing a complex POVM.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was realized that a single quantum system, such as a hydrogen atom, can transmit all three axes of a Cartesian coordinate frame [21,22]. In such schemes, the rotation matrix between the predefined reference frame and the local frame is determined by POVM measurements [23] on the exchanged quantum system.…”
Section: Introductionmentioning
confidence: 99%